Halal Tourism and Poverty Alleviation: A Case in Indonesia - Robbi Nur Fareza; Wandi Suwarno; Andika Putra (Halal Tourism and Pilgrimage, 2022)
This study discusses halal tourism, which is a type of tourism that meets Islamic sharia principles. Halal tourism is becoming increasingly popular around the world as more and more Muslim tourists are looking for tourist destinations that comply with sharia principles. This study aims to analyze the potential and development of halal tourism in Riau. This study uses the Panel Data Regression analysis method. The results showed that the variable number of tourist visits had a positive effect on the poverty rate in Riau province. The hotel occupancy rate variable has a negative and significant effect on the poverty rate in Riau province. Some of the supporting factors include the abundant halal food, the compatibility of local culture with Islamic law, and the existence of a mosque that is easy to access.